Fc Receptor-Like 1 as a Promising Target for Immunotherapeutic Interventions of B-Cell-Related Disorders. Issue 14 (November 2019) - Yousefi, Zahra; Sharifzadeh, Sedigheh; Yar-Ahmadi, Vali; Andalib, Alireza; Eskandari, Nahid
Background: Human B-cell responses are regulated through synergy between a collection of activation and inhibitory receptors. Fc receptor-like (FCRL) molecules have recently been identified as co-receptors that are preferentially expressed in human B-cells, which may also play an important role in the regulation of human B-cell responses. FCRL1 is a member of the FCRL family molecules with 2 immunoreceptor tyrosine-based activation motifs (ITAMs) in its cytoplasmic tail. This study aimed to investigate the regulatory roles of FCRL1 in human B-cell responses. Materials and methods: The regulatory potential of FCRL1 in human B-cell through knockdown of FCRL1 expression in the Ramos and Daudi Burkitt lymphoma (BL) cell lines by using the retroviral-based short hairpin ribonucleic acid (shRNA) delivery method. The functional consequences of FCRL1 knockdown were assessed by measuring the proliferation, apoptosis, and the expression levels of Bcl-2, Bid, and Bax genes as well as phosphoinositide-3 kinase/-serine-threonine kinase AKT (PI3K/p-AKT) pathway in the BL cells, using the quantitative real-time polymerase chain reaction (PCR) and flow cytometry analysis. The NF-κB activity was also measured by the enzyme-linked immunosorbent assay (ELISA). Results: FCRL1 knockdown significantly decreased cell proliferation and increased apoptotic cell death in the BL cells. There was a significant reduction in the extent of the Bcl-2 gene expression in the treated BL cells compared with control cells. On the contrary, FCRL1 knockdown increased the expression levels of Bid and Bax genes in the treated BL cells when compared with control cells. In addition, the extent of the PI3K/p-AKT expression and phosphorylated-p65 NF-κB activity was significantly decreased in the treated BL cells compared with control cells. Conclusions: These results suggest that FCRL1 can play a key role in the activation of human B-cell responses and has the potential to serve as a target for immunotherapy of FCRL1 positive B-cell-related disorders.